The Effects of Innovation, IT Advancement, GDP, and Inflation on Unemployment in OIC Countries 2013-2021 - Rizka; Taosige Wau (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2023)
Unemployment still becomes a major developmental challenge in some OIC member countries. Thus, employment determinants in those countries need to be investigated through empirical research. This study analyzes the influences of inflation, GDP, IT advancement, and innovation on unemployment in some OIC member countries. We use the purposive sampling method with criteria of countries with the past decade's average unemployment rate lower than 6%. We employ panel data from 20 countries fulfilling the requirements in 2013-2021. The panel data regression method with a fixed effect approach is used to analyze the influence of independent variables on the dependent variable. The results indicate that inflation and GDP significantly and negatively affect unemployment. On the other hand, innovation and ICT advancement have a negative but insignificant effect on the dependent variable. Regarding the results, we believe it is essential for the government as a policymaker to arrange appropriate regulations allowing industries to enhance their productivity to enlarge job opportunities and alleviate unemployment.